Desa Wisata Kemiren: Menemukenali dari Perspektif Indikator Desa Wisata dan Pariwisata Berbasis Masyarakat - Silalahi, Agnes Tresia; Asy'ari, Rifqi (TOBA: Journal of Tourism, Hospitality, and Destination, 2022)
This study aims to describe Kemiren Tourism Village through the perspective of tourism village indicators and community-based tourism. This research was conducted in Kemiren Village, Glagah District, Banyuwangi Regency. This research uses qualitative methods with data collection techniques carried out by means of observation, in-depth interviews with informants, and documentation. The results showed that the existence of the Kemiren tourist village which is a form of integration of natural and cultural tourist attractions and the strength of the community to maintain heritage, customs that are still strong and unique is maintained because of the local wisdom of the local community so that Kemiren Village has been designated as a cultural heritage to preserve his solitude. In its management, Kemiren Tourism Village applies the principle of community-based tourism. Supervision or control is carried out by the community led by a traditional leader who is very influential in holding traditions, customs and culture as well as in making decisions. In order to maintain and maintain the existence of Kemiren Village as a Tourism Village, there are several things that may need to be improved, including facilities, regeneration, and the making of written cultural rules.